Tentative identification of the phase I and II metabolites of two synthetic cathinones, MDPHP and α‐PBP, in human urine. Issue 10 (13th July 2020) - Kavanagh, Pierce; Gofenberg, Mariia; Shevyrin, Vadim; Dvorskaya, Oksana; Dowling, Geraldine; Grigoryev, Andrej
Abstract: Cathinone derivatives are one of the more prominent groups of new psychoactive substances in terms of the number of forensic case reports and the variety of chemical structures available. These substances often sold as "bath salts" are classified as psychostimulants. Using liquid chromatography‐high resolution mass spectrometry, the metabolites of two pyrrolidine cathinone derivatives, α‐PBP and the less common MDPHP, were tentatively identified in urine samples collected from patients admitted to hospital following drug intoxications. The major metabolic pathways for α‐PBP and MDPHP were similar to those of their more common analogs (α‐PVP and MDPV). Metabolites arising from hydroxylation, reduction of the carbonyl group to an alcohol, oxidation to form a lactam and subsequent ring‐opening, and a combination of these processes were identified. In addition, biotransformations of the benzodioxole moiety in MDPHP included demethylenation with subsequent methylation and carboxylation of the butyl group. The majority of the hydroxylated metabolites of α‐PBP and MDPHP were found to be glucuronidated. Both α‐PBP and MDPHP undergo extensive metabolism and the chromatographic peak areas of the metabolites were found to be comparable to or exceeded those of the parent substances. Metabolites resulting from demethylenation and subsequent methylation (MDPHP), reduction of carbonyl group (α‐PBP), and oxidation to form a lactam combined with ring‐opening (α‐PBP and MDPHP) were found to be the most useful target analytes for the confirmation of ingestion. Abstract : The phase I and II metabolites of the two synthetic cathinones, MDPHP and α‐PBP, were tentatively identified by high‐resolution LCMS/MS in human urine samples. Both compounds undergo extensive metabolism and major metabolic pathways include opening of the pyrrolidine and dioxole rings.